Business statistics : an inferential approach - Dietrich, Frank H.; Shafer, Nancy J. (San Francisco, Calif. : Dellen Pub. Co., 1984)
This book is designed for an introductory course in business statistics. The text is intended for students who do not have a strong mathematical background; a second-year high school algebra course should be sufficient. The theme of this text is statistical inference.
Includes index.
rpm 24/01/2019, ijb 28/02/2019
Loans
Keywords: Commercial statistics